2011
DOI: 10.1098/rspb.2011.1968
|View full text |Cite
|
Sign up to set email alerts
|

Parallel changes in mate-attracting calls and female preferences in autotriploid tree frogs

Abstract: For polyploid species to persist, they must be reproductively isolated from their diploid parental species, which coexist at the same time and place at least initially. In a complex of biparentally reproducing tetraploid and diploid tree frogs in North America, selective phonotaxis-mediated by differences in the pulserepetition (pulse rate) of their mate-attracting vocalizations-ensures assortative mating. We show that artificially produced autotriploid females of the diploid species (Hyla chrysoscelis) show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
(74 reference statements)
2
33
1
Order By: Relevance
“…Taking this into account, the behavioral preference of females for different pulse repetition rates in di-, tri-, and tetraploid specimen of the Hyla chrysoscelis complex might be a consequence of different genome sizes, which affect cell dimensions (Keller and Gerhardt 2001;Tucker and Gerhardt 2012). Moreover, electrophysiological recordings in the torus of B. bombina (11.38 pg) with large neurons and R. temporaria (4.26 pg) with smaller neurons indicate that neurons in B. bombina do not synchronize to high stimulus pulse repetition rates as do neurons in R. temporaria (Walkowiak 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Taking this into account, the behavioral preference of females for different pulse repetition rates in di-, tri-, and tetraploid specimen of the Hyla chrysoscelis complex might be a consequence of different genome sizes, which affect cell dimensions (Keller and Gerhardt 2001;Tucker and Gerhardt 2012). Moreover, electrophysiological recordings in the torus of B. bombina (11.38 pg) with large neurons and R. temporaria (4.26 pg) with smaller neurons indicate that neurons in B. bombina do not synchronize to high stimulus pulse repetition rates as do neurons in R. temporaria (Walkowiak 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the genetic architecture underlying pulse rate and pulse number is expected to be complex, potentially involving many genes. What is known about the genomic basis of frog calls is that gene dosage affects frog signals-ploidy level is correlated with trait values (Guignard, Büchi, Gétaz, Betto-Colliard, & Stöck, 2012;Hoffman & Reyer, 2013;Keller & Gerhardt, 2001;Mable & Bogart, 1991;Tucker & Gerhardt, 2012). More is known about the genetic architecture of acoustic signals in insects-for example, in crickets several quantitative trait loci have been identified that control pulse rate (Ellison, Wiley, & Shaw, 2011;Shaw & Lesnick, 2009;Shaw, Parsons, & Lesnick, 2007).…”
Section: Acoustic Signals Hybrid Index and Admixture Levelsmentioning
confidence: 99%
“…This finding is important in light of earlier work on the roles of hormones in the mate choice behaviors of female frogs [6, 31, 46, 47]. Several previous studies have shown that hormone administration can induce sexual proceptivity in female frogs [13, 32, 33, 42-44, 50, 63, 64]. Only three previous studies of only two species ( H. versicolor and Physalaemus pustulosus ) have shown that hormone administration can induce species-typical patterns of sexual selectivity in the context of intraspecific mate choice [13, 32, 33].…”
Section: Discussionmentioning
confidence: 53%